Pengembangan Bahan Ajar Fikih Berbasis Canva Untuk Meningkatkan Minat Belajar Siswa Di MTsS Al-Ikhlas Tigaraksa Kabupaten Tangerang - Fauziah, Neneng; Asphandi; Hidayatullah (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research aims to develop Canva-based Jurisprudence teaching materials as an alternative to increase student learning motivation. The research method used is development research (Research and Development) with steps to adapt the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection was conducted through observation, interviews, and questionnaires. The respondents of this study were grade 7 students at MTsS Al-Ikhlas Tigaraksa, Tangerang Regency. The results showed that Fiqik teachers at MTsS Al-Ikhlas Tigaraksa Tangerang have not used canva-based teaching materials, so the interest of students tends to be less. So Jurisprudence teaching materials on congregational prayer were developed in the form of canva-based PPT presentations. After implementation, it is found that the interest of students tends to increase. The development of canva-based teaching materials is still simple, only in the form of PPT which is designed in such a way that it is easy to use by teachers and can increase students' interest in learning. In addition to PPT, Canva can also create other types of teaching materials, such as Images, videos, E-Books, Modules, Benner and Leaflets. The Canva platform can also be used as an online learning medium or E-Learning.